Circulating Branched Chain Amino Acid Concentrations Are Higher in Dairy-Avoiding Females Following an Equal Volume of Sheep Milk Relative to Cow Milk: A Randomized Controlled Trial - Milan, Amber M.; Samuelsson, Linda M.; Shrestha, Aahana; Sharma, Pankaja; Day, Li; Cameron-Smith, David (Frontiers in Nutrition, 2020)
Background: Intolerances to bovine dairy are a motivating factor in consumers seeking alternate - or replacement - dairy beverages and foods. Sheep milk (SM) is an alternate dairy source, with greater protein, although similar amino acid composition compared to cow milk (CM). Studies are yet to address the appearance of circulating amino acids following consumption of SM, relative to CM, in humans. Objective: To clinically determine the appearance of branched chain amino acids, and other amino acids, in circulation in response to equal servings of SM and CM, in females who avoid dairy products. Design: In a double-blinded, randomised, cross-over trial, 30 self-described dairy avoiding females (20-40 years) drank 650 mL of SM or CM that were reconstituted from the spray dried powders (30 and 25 g in 180 mL water, respectively) on separate occasions, following an overnight fast. After reconstitution, the energy and protein provided by SM was higher than for CM (2140 vs. 1649 kJ; 29.9 vs. 19.4 g protein); content of branched chain amino acids (BCAAs) were 10.5 and 6.5 mg/mL, respectively. Blood samples were collected at fasting and at regular intervals over 5 h after milk consumption. Plasma amino acids were measured by HPLC. Results: 80% of subjects self-identified as lactose intolerant, and the majority (47%) “avoided drinking milk” “most of the time”. SM resulted in greater plasma appearance of BCAAs at 60 min (641.1 ± 16.3 vs. 563.5 ± 14.4 µmol/L; p<0.001) compared with CM. SM similarly resulted in elevated postprandial concentrations of the amino acids lysine, methionine and proline, particularly at 240 min (time × milk interactions p=0.011, 0.017, and p=0.002, respectively). Postprandial increases in plasma alanine concentrations were sustained to 120 min after CM (time × milk interaction p=0.001) but not after SM, despite greater quantities provided by SM. Conclusions: SM is a rich source of protein, and relative to CM, provides a greater quantity of BCAAs, with a corresponding elevation of the postprandial circulating BCAA response. SM is therefore a possible dairy alternative of benefit to those who need to increase total protein intake or for individuals with heightened protein requirements.